1985
DOI: 10.1677/joe.0.1070437
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous opioid peptides and hypothalamic neuroendocrine neurones

Abstract: This consideration of the influence of endogenous opioid peptide systems on GnRH and oxytocin neurones serves to illustrate some of their possible regulatory interactions with other neuroendocrine systems. Opioids are known to influence the secretion of all the anterior pituitary hormones (see Grossman & Rees, 1983) and these effects are likely to be mediated, at least in part, in the hypothalamus. For example, inhibitory effects of opioids have also been described on secretion from the median eminence of soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(56 citation statements)
references
References 82 publications
(107 reference statements)
1
52
0
3
Order By: Relevance
“…Our experimental conditions cannot clarify the site of action of the opiate/GABA/BZD interactions in the inhibition of exercise-stimulated ACTH secretion. The effect of ALP might be exerted at the pituitary level, where opioids are known to reduce ACTH secretion or in the hypothalamus where endogenous opioids are thought to inhibit corticotrophin releasing hormone (CRH) release [7,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental conditions cannot clarify the site of action of the opiate/GABA/BZD interactions in the inhibition of exercise-stimulated ACTH secretion. The effect of ALP might be exerted at the pituitary level, where opioids are known to reduce ACTH secretion or in the hypothalamus where endogenous opioids are thought to inhibit corticotrophin releasing hormone (CRH) release [7,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies utilizing opiate agonists and antagonists have demonstrated that endogenous opioid peptides inhibit LH and stimulate prolactin (Meites et al, 1979;Grossman & Rees, 1983;Bicknell, 1985;Malven, 1986). Administration of naloxone, an opioid antagonist, during lactation resulted in increased LH in rats (Sirinathsinghji & Martini, 1984), ewes (Gregg et al, 1986), cows , women (Ishizuka et al, 1984) and sows Mattioli et al, 1986) and suppressed serum prolactin in rats (Ferland et al, 1978;Miki et al, 1981;Sirinathsinghji & Martini, 1984), ewes (Gregg et al, 1986) and sows (Mattioli et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence implicate endogenous opioid peptides in the regulation of puberty (Wilkinson and Bhanot, 1982;Bhanot and Wilkinson, 1983;Sirinathsinghji et al, 1985;Rodriguez et al, 1993), secretion of luteinizing hormone (Cicero et al, 1979;Kalra and Kalra, 1984;Piva et al, 1985;Zhen and Gallo, 1992) through alterations of luteinizing hormone-releasing hormone (LHRH) release (Bicknell, 1985;Kalra, 1986;Piva et al, 1986;Jacobson and Kalra, 1989), and female sexual behavior (Wiesner and Moss, 1986a,b;Pfaus and Gorzalka, 1987;Vathy et al, 1991;Pfaus and Pfaff, 1992;Allen et al, 1993;Olster, 1994;Torii et al, 1995Torii et al, , 1996Sinchak et al, 1997a). Endogenous opioid peptides also modulate the estrogeninduced expression and release of other transmitters that alter reproductive behavior, such as cholecystokinin and substance P (Eckersell and Micevych, 1997;Sinchak et al, 1997b), norepinephrine (Vathy et al, 1991), and serotonin (Allen et al, 1993).…”
mentioning
confidence: 99%